Efficacy and safety evaluation of avatrombopag in immune thrombocytopenia: analyses of a phase III study and long-term extension. (17th February 2022) - Al‐Samkari, Hanny; Nagalla, Srikanth
Abstract: Avatrombopag is an oral thrombopoietin receptor agonist approved for chronic immune thrombocytopenia (ITP). This is a post hoc analysis of the pivotal phase III study (NCT01438840) evaluating additional endpoints not previously described. Thirty-two ITP patients were randomized to avatrombopag and 17 were randomized to placebo during a 26-week core study period (with 21 study visits), followed by an open-label extension period, in which all patients received avatrombopag for varying lengths of time. In this analysis, we evaluated previously unreported response rates at the study visit level, durability of response, and reduction in corticosteroid use with avatrombopag treatment. In the core study, more avatrombopag-treated patients achieved either response (Plt ≥50 000/µL) or complete response (Plt ≥100 000/µL) than placebo-treated patients by day 8 (65.6% vs. 0%; P < .0001 for response; 37.5% vs. 0%; P < .0001 for complete response), day 28 (84.4% vs. 0%; P < .0001 for response; 71.9% vs. 0%; P < .0001 for complete response), and month 6 (87.5% vs. 5.9%; P < .0001 for response; 81.3% vs. 5.9%; P < .0001 for complete response). Durable responders from the core study achieved response and complete response at 96.1% and 60.1% of extension phase visits, respectively. Durable clinically relevant response (Plt ≥30 000/µL for 6 of the final 8 weeks of the core study) occurred in 64.0% of avatrombopag-treated patients versus 0% of placebo-treated patients. More than half (57.1%) of patients on chronic corticosteroids reduced or discontinued corticosteroids. In conclusion, avatrombopag enabled most patients with ITP to achieve clinically meaningful and durable platelet count improvements.